PERCEPTION LISTENING SKILLS OF SECOND SEMESTER PHYSICAL EDUCATION STUDENTS THROUGH FOOTBALL COMMENTARIES - vihky fariski (CV Grasta Glory, 2025)
The purpose of this study was to evaluate the effectiveness of English commentator communication skills in improving academic performance during two semesters of the Physical Education Study Program. Through two phases of the Classroom Action Research (CAR) method, students were given information about authentic materials, such as football commentary. The results of the questionnaire and tests showed that the majority of respondents experienced significant improvements in their understanding of English, their grammatical knowledge, and their understanding of the context of the game, including strategy and tactics. The majority of respondents also said that they had higher expectations for this teaching method than the traditional classroom method. Therefore, the use of football commentary as a teaching tool is quite effective, contextual, and in-depth, although not all students immediately gave positive responses. This approach is best described as a complementary method to the commodification of various learning styles of students.